An Empirical Study on Attrition & Employee Retention Initiatives With Reference To Flow Link Systems Private Limited, Coimbatore (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
Employee retention and turnover are topics of a lot of conversations centering on HR. The challenge for the HR professionals today is not only to attract and attain the right employees, but also to innovatively train them. The research was conducted in Flow link systems Pvt Ltd which comes under metal casting industries. The company is located in Arasur which is started as the foundry division and is continued to expand to the present level. Total employees are 655 and, the researcher has selected 150 samples through stratified disproportionate random sampling method. The researcher has found that the employees are highly satisfied with the work load and lead time and working environment, relationship between supervisors and colleagues are neutral. Employees are dissatisfied with their training and development, salary structure and the suggestions are made by the researcher for the same to retain the employees towards their work.